Suicide prevention in Hong Kong: pushing boundaries while building bridges - Paul Siu Fai Yip; Eric D. Caine; Cheuk Yui Yeung; Yik Wa Law; Rainbow Tin Hung Ho (Elsevier, 2024)
Summary: Hong Kong is a natural laboratory for studying suicides-small geographic footprint, bustling economic activity, rapidly changing socio-demographic transitions, and cultural crossroads. Its qualities also intensify the challenges posed when seeking to prevent them. In this viewpoint, we showed the research and practices of suicide prevention efforts made by the Hong Kong Jockey Club Centre for Suicide Research and Prevention (CSRP), which provide the theoretical underpinning of suicide prevention and empirical evidence. CSRP adopted a multi-level public health approach (universal, selective and indicated), and has collaboratively designed, implemented, and evaluated numerous programs that have demonstrated effectiveness in suicide prevention and mental well-being promotion. The center serves as a hub and a catalyst for creating, identifying, deploying, and evaluating suicide prevention initiatives, which have the potential to reduce regional suicides rates when taken to scale and sustained.